Recasting Persian poetry : scenarios of poetic modernity in Iran - Karimi-Hakkak, Ahmad (University of Utah Press, 1995)
"Using a semiotic model of poetic change, Recasting Persian Poetry presents a critical history of the evolution of Persian poetry in modern Iran. Iran's contact with Europe in the nineteenth century produced largely imaginary ideas about European culture and literature. In a series of textual maneuvers and cultural contestations, successive generations of Iranian intellectuals sought to recast the classical tradition in a mold at once modern and relevant to their concerns." "In particular, Karimi proposes a revision of the view that sets the Modernist poet Nima Yushij as the single-handed inventor of "New Poetry." This view, he argues, has resulted in an exaggerated sense of the esthetic gulf between the modernist poetry of Iran and classical Persian poetry." "Through a number of close readings of works by Nima's predecessors, Karimi makes visible a century-old Persian poetic tradition with Nima as its culmination."--Jacket